Edukasi Berbasis Video terhadap Tingkat Kecemasan Pasien Pre Kateterisasi Jantung - Handayani, Eneng Hilda; Danismaya, Irawan; Safariyah, Erna; Basri, Burhanuddin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effect of video-based education on anxiety levels among patients undergoing pre-cardiac catheterization. The research employed a pre-experimental one-group pretest–posttest design and data were analyzed using the Wilcoxon signed-rank test, which is commonly used to compare paired pretest–posttest data in similar intervention studies. The findings indicated a statistically significant difference in anxiety levels before and after the provision of video-based education (p-value 0,000). In conclusion, video-based education was associated with a reduction in anxiety levels among patients scheduled for cardiac catheterization Keywords: Anxiety, Cardiac Catheterization, Education, Video